Fessenden of Maine : Civil War Senator - Jellison, Charles A. (Charles Albert), 1924- (Syracuse, N.Y., Syracuse University Press, 1962)
"Entering the Senate during the convulsive Kansas-Nebraska debate, William Pitt Fessenden rose to a place of leadership among that small band of anti-Nebraska Congressmen who then swung their support to the infant Republican party. Until his death in 1869 Senator Fessenden occupied a commanding position in national councils, where his powerful intellect, mastery in debate, and unquestioned integrity caused him to be considered by many of his colleagues as the foremost legislator of his day."
Bibliography: p. 274-284.
Keywords: Fessenden, William Pitt, -- 1806-1869.; Kansas-Nebraska debate -- Biography; Republican party -- Biography